Sunday

April 20, 2014

April 20, 2014

Posted by **mae** on Monday, January 11, 2010 at 7:41pm.

- algebra -
**Ms. Sue**, Monday, January 11, 2010 at 7:44pm3(q+1)-9=23

3q + 3 - 9 = 23

3q = 23 - 3 + 9

3q = 29

q = 9 2/3

- algebra -
**Natalie**, Monday, January 11, 2010 at 7:47pm3(q+1)-9=23

3q+3-9=23

3q-6=23

3q=29

__

q=9.66

- algebra -
**mae**, Monday, January 11, 2010 at 8:13pmthank you

- algebra -
**Ms. Sue**, Monday, January 11, 2010 at 8:16pmYou're welcome.

**Related Questions**

Algebra -polynomial - Solve the polynomial 40x^2+2x-65 Notice that for x = 1 the...

Algebra 1A - SIMPLIFY: 9-6*11-17= DIVIDE IF POSSIBLE 3-/23/(1/-23SELECT THE ...

algebra - On the problem 9x+7y=4 x=23-4y solve by substitution Do you mean to ...

Algebra - Find the smallest positive integer N \neq 23 such that the fraction \...

Algebra - Find the smallest positive integer N \neq 23 such that the fraction \...

algebra - Which properties did Carmen use to solve the following problem? 17 + (...

Consumer Math - The quoient of 5/31 divided by 15/23 , reduced to lowest ...

math - The quotient of 5/31 divided by 15/23, reduced to the lowest fraction, is...

Algebra - Hello, can someone tell me if I got the following solve and check work...

algebra - Janet invested $23,000, part at 6% and part at 17%. If the total ...